TfVPS32 Regulates Cell Division in the Parasite Tritrichomonas foetus. (7th June 2017) - Iriarte, Lucrecia S.; Midlej, Victor; Frontera, Lorena S.; Moros Duarte, Daniel; Barbeito, Claudio G.; de Souza, Wanderley; Benchimol, Marlene; de Miguel, Natalia; Coceres, Veronica M.
Abstract: The flagellated protist Tritrichomonas foetus is a parasite that causes bovine trichomonosis, a major sexually transmitted disease in cattle. Cell division has been described as a key player in controlling cell survival in other cells, including parasites but there is no information on the regulation of this process in T. foetus . The regulation of cytokinetic abscission, the final stage of cell division, is mediated by members of the ESCRT (endosomal sorting complex required for transport) machinery. VPS32 is a subunit within the ESCRTIII complex and here, we report that TfVPS32 is localized on cytoplasmic vesicles and a redistribution of the protein to the midbody is observed during the cellular division. In concordance with its localization, deletion of TfVPS32 C‐terminal alpha helices (α5 helix and/or α4‐5 helix) leads to abnormal T. foetus growth, an increase in the percentage of multinucleated parasites and cell cycle arrest at G2/M phase. Together, these results indicate a role of this protein in controlling normal cell division.